Monitoring student education and confidence in LGBTQ+ health in UK medical schools. (November 2022) - Phillips, Callum; Lazzereschi, Lucia; Griksaitis, Michael
Objectives: We sought to evaluate and describe UK medical students' experiences of education in LGBTQ+ (lesbian, gay, bisexual, transgender and queer) health and their confidence in approaching these consultations and identify any perceived gaps in medical school curricula. We also sought to examine whether individual identity affected medical students' clinical practice. Method: A 19-question questionnaire collecting quantitative and qualitative responses was sent to all medical students in the UK. Results: A total of 307 students completed the questionnaire; 36% ( n = 184) reported no dedicated teaching on LGBTQ+ health issues/inequalities and 88% ( n = 267) reported no LGBTQ+-specific communication skills training. Respondents found it more challenging to discuss LGBTQ+ health issues with patients compared to performing clinical examinations on LGBTQ+ patients. In the clinical environment, students were more likely to ask about sexual orientation, gender identity and pronouns within the context of sexual health over psychiatric, surgical and medical consultations. Measured via a Likert-type scale from 0 to 100, students felt LGBTQ+ health teaching should be given higher importance within the curriculum (74/100) than their medical school currently placed on it (13/100). Ninety-five percent of students stated that they needed further education on LGBTQ+ health. Conclusion: Findings suggest that at a national level, UK medical students do not feel well equipped to deal with LGBTQ+ health issues, and despite students' recognition of the importance of this topic, this is not matched by curricular provision. Students report having difficulty discussing LGBTQ+ health issues and performing examinations on LGBTQ+ patients. Further training on LGBTQ+ health and actions to increase student confidence could help improve LGBTQ+ patient outcomes and improve the relationship between patients and clinicians. Students should be consulted in the re-development of relevant curricula.